COMPLEMENTARY FEEDING PRACTICES OF OLDER INFANTS ATTENDING CHILD WELFARE CENTRE IN A SOUTH WESTERN TOWN, NIGERIA - Anaemene, D. I.; Sogunle, W. O. (FUDMA JOURNAL OF SCIENCES, 2020)
Under-nutrition among children is worse during the complementary feeding period and results in high morbidity, irreversible complications, and death. This study examined the complementary feeding practices and nutritional status of older infants (6 – 24 months) attending the child welfare clinic in Ota State Hospital, Ogun State. The study was a descriptive cross-sectional study. Weight,length and Mid Upper Arm Circumference (MUAC) measurements of 152 children were taken according to standard procedures to calculate the weight for age, weight for length, length for age z-scores using WHO Anthro software. A food frequency questionnaire was used to elicit information on the complementary feeding practices of the children. Exclusive breastfeeding rate among these mothers was 57%. Early (≤ 3 months), timely (4-6 months) and late (≥ 7 months) introduction of complementary foods were observed in 11.8%, 42.8% and 45.4% of the children, respectively. The most common food offered as the first complementary food was pap (31.6%), followed by commercial cereal-based complementary foods (23.7%) and infant formula (15.1%). Children consumed more cereals either as local or commercial based (79.5%), followed by meat/fish (64.7%), and milk/milk products (63.2%). However, daily, a greater number of children were given commercial cereal-based complementary foods (24.3%) compared to local cereal-based complementary foods (19.7%). Minimum meal frequency was met by 86.8 percent of the children while the majority of the children did not meet minimum dietary diversity. About 48%, 40.7% and 38.9% of the children were wasted, underweight and stunted, respectively. Under-nutrition particularly wasting was high among the children.